Advances of hydrogel combined with stem cells in promoting chronic wound healing - Li, Qirong; Wang, Dongxu; Jiang, Ziping; Li, Rong; Xue, Tianyi; Lin, Chao; Deng, Yongzhi; Jin, Ye; Sun, Baozhen (Frontiers in Chemistry, 2022)
Wounds can be divided into two categories, acute and chronic. Acute wounds heal through the normal wound healing process. However, chronic wounds take longer to heal, leading to inflammation, pain, serious complications, and an eco-nomic burden of treatment costs. In addition, diabetes and burns are common causes of chronic wounds that are difficult to treat. The rapid and thorough treatment of chronic wounds, including diabetes wounds and burns, represents a significant unmet medical need. Wound dressings play an essential role in chronic wound treatment. Various biomaterials for wound healing have been developed. Among these, hydro-gels are widely used as wound care materials due to their good biocompatibility, moisturizing effect, adhesion, and ductility. Wound healing is a complex process in-fluenced by multiple factors and regulatory mechanisms in which stem cells play an important role. With the deepening of stem cell and regenerative medicine research, chronic wound treatment using stem cells has become an important field in medical research. More importantly, the combination of stem cells and stem cell derivatives with hydrogel is an attractive research topic in hydrogel preparation that offers great potential in chronic wound treatment. This review will illustrate the development and application of advanced stem cell therapy-based hydrogels in chronic wound healing, especially in diabetic wounds and burns.